Estudio de la Enfermedad Renal en perros - Calero Vega, Pamela Dayana (2023)
In this document we want to describe the Study of Kidney Disease in dogs, this refers to a disease that affects one or both kidneys causing alterations in their functioning. As we know, the kidneys are in charge of filtering the blood and thus eliminate the substances of desire through urine. When a failure occurs in this system, what can happen is that the body will try to compensate for it, so that we will not observe symptoms until the damage is very advanced. Thus, kidney disease in dogs can manifest acutely or chronically. The most common symptoms, polydipsia (increased water intake) and polyuria (increased urination), will occur in both cases. The difference is that in the acute onset the symptoms will manifest suddenly, causing a serious clinical picture. In the chronic, the symptoms are maintained for months in which the kidneys deteriorate until they can no longer take it, which affects the entire organism and ends up causing the death of the animal; on the other hand, renal failure in dogs older than 10 years has a considerable incidence, unlike in young dogs; As for elderly dogs, it is possible that the symptom is urinating at home. For this reason, it is important that dogs, from 7 years of age, go to the vet at least once a year to detect these diseases early.